HAARP conspiracy: Analysis of its role in the 2023 Turkey & Syria earthquakes on Twitter - Arce-García, Sergio; Díaz-Campo, Jesús (Estudios sobre el Mensaje Periodístico, 2024)
The twenty years that went from 1990, with the apparition of the private networks, and 2006, with the consolidation of the new model of public television established in the State Broadcasting Companies Law, were very difficult for RTVE. The public television had to adapt to a completely new media environment and do so on the fly and with very scarce resources. The company tried to maintain the quality of programming as its brand signature, while competing with private networks focused of purely commercial contents which tried to conquer the audience that was fleeing RTVE in droves. This research analyses which were the keys of this quality content through a sample of 91.610 emissions. The contents have been categorized in genres, subgenres and programming blocks, so as to establish how many minutes were dedicated to each category and how this distribution evolved through the two decades. We have also studied the changes in the audiences and in the discourse that TVE had about itself.
Keywords: Haarp; earthquake; disinformation; conspiracy theories; Twitter